Improving work placement for international students, their supervisors and other stakeholders : final report 2016. - Barton, Georgina; Hartwig, Kay; Cain, Melissa (Australian Department of Education and Training, 2017)
Report from the WISP project which endeavoured to improve work placement components of study programs for international students in Australia. In particular the researchers: identified current procedures and practices in relation to work-placement and associated assessment for international students in the discipline areas of Business, Education, Engineering, and Health in participating institutions; identified and explored challenges, concerns and successes for international students, their mentors (i.e. those people who are responsible for assessing and working with students during their placement) and coordinators (i.e. those people responsible for the coordination of placements, at both universities and workplaces) prior to, during and after the students leave; and developed and applied a working model of effective practice around internationalisation, work-place socialisation and reflection. The model provided a theoretical and evidence-based foundation in the development of support materials for current and prospective international students, their supervisors, coordinators and relevant university staff. Six universities participated in the project. [p.iii, ed]